Tawdzīf al-Nushush al-Adabiyyah fī Ta’allumi al-Lughah al-‘Arabiyyah Ladā al-Thullāb al-Nāthiqīn Bighairihā - Siti Amirah Nurul 'Ain Mohd Bulkhaini (LISANUDHAD: JURNAL BAHASA, PEMBELAJARAN DAN SASTRA ARAB, 2022)
Using literary texts is one of the creative approaches that we can use in learning Arabic language. This creative approach is in line with learning methods using diverse literary texts from poetry and prose texts such as novels and short stories to improve the competence of non-Arabic speaking students. This study aims to reveal literary texts for being the creative approach that raised motivation in learning Arabic language among non-Arabic speakers, and to show the use of literary texts in developing students' language skills. To achieve the objectives of the research, the researcher used the systematic review of the previous study (Systematic Literature Review), where she analyzes the data in an objective form. One of the most important findings of the research is that the use of literary texts in learning Arabic language helps non-native speakers improve their language skills, especially in Arabic grammar and morphological forms, and it also helps them acquire new vocabulary and good methods that students can benefit it. Based on this, teachers should focus on choosing appropriate literary texts, including using novels and short stories in learning Arabic language, to ensure that students understand the rules better and can practice them. In conclusion, the research recommended the necessity of cultivating interest in non-native speakers in the use of literary texts to increase the level of understanding and the ability to remember Arabic grammar, in addition to improving the skill of reading and writing in Arabic, which ensures a better lifelong learning.